Learning Motivation and Authoritative Parenting for Self-Regulated Learning: The Mediation of Self-Efficacy - Malau, Martha; Indartono, Setyabudi; Tianawati, Arum Khairunisa Agus (Jurnal Pendidikan Indonesia, 2022)
Self-regulated learning was one of the factors that can determine the success of learning in the application of online learning during the COVID-19 pandemic. However, researchers have not thoroughly discussed the factors of individual learning (learning motivation and self-efficacy) and social influences (authoritative parenting) that can develop students' self-regulated learning skills. This study aims to analyze the effect of learning motivation and authoritative parenting on self-regulated learning through self-efficacy as a mediator. This study used a quantitative approach, and the number of respondents was 310 students of class XI Social Science High School. Respondents were selected based on the proportional random sampling technique. Data were analyzed using multiple regression with SPSS 22. The results showed that self-efficacy partially mediated the effect of learning motivation and authoritative parenting on self-regulated learning. The results of this study provide theoretical development and make it easier for educational institutions, school principals, teachers, students, and parents to obtain information related to self-regulated learning during the COVID-19 pandemic.